2012
DOI: 10.1103/physrevb.85.184432
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic order and domains in Sr3Ir2O7probed by x-ray resonant scattering

Abstract: We report on a detailed x-ray resonant scattering study of the bilayer iridate compound Sr 3 Ir 2 O 7 at the Ir L 2 and L 3 edges. Resonant scattering at the Ir L 3 edge has been used to determine that Sr 3 Ir 2 O 7 is a long-range ordered antiferromagnet below T N ≈ 230 K with an ordering wave vector q = ( 1 2 , 1 2 ,0). The energy resonance at the L 3 edge was found to be a factor of ∼30 times larger than that at the L 2 edge. This remarkable effect has been seen in the single-layer compound Sr 2 IrO 4 and h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
116
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(129 citation statements)
references
References 25 publications
10
116
3
Order By: Relevance
“…For example, the sizable c-axis component of the uniform magnetic susceptibility is not understood and seems incompatible with the known magnetic structure of Sr 2 IrO 4 . In addition, the diamagnetism initially reported for Sr 3 Ir 2 O 7 is completely unexplained and is absent in samples grown under different conditions [27][28][29] . Therefore, we believe it is imperative to establish the intrinsic magnetic properties through growth of stoichiometric single crystals of the parent iridates before the doping-induced phenomena can be fully explored.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, the sizable c-axis component of the uniform magnetic susceptibility is not understood and seems incompatible with the known magnetic structure of Sr 2 IrO 4 . In addition, the diamagnetism initially reported for Sr 3 Ir 2 O 7 is completely unexplained and is absent in samples grown under different conditions [27][28][29] . Therefore, we believe it is imperative to establish the intrinsic magnetic properties through growth of stoichiometric single crystals of the parent iridates before the doping-induced phenomena can be fully explored.…”
Section: Introductionmentioning
confidence: 88%
“…Moreover, we note that previous studies on the parent Sr 2 IrO 4 and its sister compounds have shown significant variations in the magnetic properties even without doping, likely reflecting different defect concentrations 2,4,18,[22][23][24][25][26][27][28][29] . For example, the sizable c-axis component of the uniform magnetic susceptibility is not understood and seems incompatible with the known magnetic structure of Sr 2 IrO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, similar to Sr 2 IrO 4 , Sr 3 Ir 2 O 7 is a G-type antiferromagnet at low temperature [5,6,7]. However, there remains some controversy over the details of the precise magnetic structure reported in the recent literature, and explanations of certain aspects of the bilayered system that are present in the experimental data [5,6,7,8]. This article reports an investigation of the antiferromagnetic structure with an in-depth study of the azimuthal and polarisation dependent resonant scattering signal with particular consideration of the domain behaviour, resulting as a consequence of the degeneracy of two magnetic propagation vectors k 1 =( 1 2 , 1 2 ,0) and The intensity of the ( 1 2 , 1 2 ,24) reflection, corresponding to the k 1 =( 1 2 , 1 2 ,0) magnetic propagation vector, has been measured as a function of x and y sample position in a temperature sequence T=90 K, 300 K, 90 K. The bright yellow regions are areas of high intensity and the dark areas are close to zero intensity.…”
mentioning
confidence: 99%
“…Bulk magnetisation data in the 5 K to 300 K temperature interval reveals three distinct transitions at ∼280 K, ∼230 K and ∼50 K [10,12,5], although it should be noted that the precise values of these transitions vary by as much as 10 K from study to study. Our previous x-ray scattering investigation of this compound [5], combined with calculations performed using the SARAh program [13], which calculates irreducible representations based on symmetry analysis and group theory, indicated that Sr 3 Ir 2 O 7 displays a two-domain Gtype antiferromagnetic structure with wave vectors k 1 =( 1 2 , 1 2 ,0) and k 2 =( 1 2 ,-1 2 ,0). These two modulation vectors are represented by symmetry-related structures, denoted A and B in Figure 6 of Boseggia et al [5], and result in magnetic Bragg peaks at ( 1 2 , 1 2 ,L=even) and ( 1 2 , 1 2 ,L=odd) positions, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation